Upaya Pendekatan Kedokteran Keluarga pada Perempuan 42 Tahun dengan DM Tipe 2 di Aceh Utara - Nadia Alkhalifa; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
The patient came with complaints of frequent tingling in both legs for 2 months. These complaints were accompanied by a body that continuously felt weak even though the patient did not do heavy activities. The patient also complained of nausea but no vomiting, frequent urination especially at night, and often felt thirsty. Other complaints such as fever and bowel disorders were denied by the patient. The patient also did not routinely use insulin medication. Primary data were obtained through autoanamnesis and physical examination by conducting home visits, filling out family folders, and filling out patient files. The assessment was carried out based on the initial holistic diagnosis, process, and end of the visit quantitatively and qualitatively. The interventions carried out included education about the causes of diabetes mellitus to his family, education about lifestyle modification and management of the disease, and explaining complications that may arise from the patient's disease so that the patient takes regular treatment and makes preventive efforts.